Rufinamide in Children with Refractory Epilepsy: Pharmacokinetics, Efficacy, and Safety - Dahlin, Maria G.; Ohman, Inger (Neuropediatrics, 2012)
We examined the influence of age and type of concomitant antiepileptic drugs (AEDs) on the pharmacokinetics of rufinamide (RUF) as well as its efficacy and safety in 51 children with refractory epilepsy. In a retrospective noninterventional survey, dose-to-concentration ratios of RUF and concomitant AEDs were calculated: the weight-normalized dose (mg/kg/d) divided by the steady-state trough plasma drug level, which was used as a measure of clearance. During treatment with RUF concomitantly with valproic acid (VPA) young children, aged 0 to 4.9 years, had a low clearance of RUF, which did not differ from older children. If not on VPA but on enzyme inducers, young children had a threefold higher clearance of RUF than the older ones. In young children not on VPA, those on enzyme inducers had 1.7-fold higher clearance than those on nonenzyme inducers. In children neither on VPA nor on enzyme inducers, RUF clearance was age-dependent with higher clearance in younger children. Adding RUF did not change the pharmacokinetics of concomitantly used AEDs. Seizure response after 2 to 3 months on RUF treatment was found in 12 of 51 children (23.5%), at mean plasma level of 36.9 ± 22.0 µmol/L. Adverse events were reported in 41% of the patients of which fatigue was most frequent (24%).
Keywords: rufinamide; plasma level; dose-to-concentration ratio; clearance; child; age; VPA; enzyme inducer